South African Heart Association Position Statement for the management of valvular heart disease – Part I - Meel, R; Cupido, B; Hitzeroth, J; Ofoegbu, C; Viljoen, C; Bisetty, P; Lawrenson, J; van der Bijl, P (SA Heart Journal, 2026)
The burden of valvular heart disease (VHD) remains high in South Africa and is associated with considerable morbidity and mortality. While a decline in acute rheumatic fever cases has been observed, chronic rheumatic VHD remains an important cause of index heart failure admission in South Africa. Additionally, with the increased longevity of the African population, degenerative VHD has emerged as an important aetiology. To date, data about VHD epidemiology, diagnosis, management, and patient follow-up remain scarce in this region. Patients with VHD and their physicians face unique challenges in the South African setting. Hence, in this Position Statement, we aim to provide the general cardiologist with a comprehensive review to complement existing guidelines on VHD for adequate patient management in the local setting. This document will comprise 2 parts. Part I focuses on the evaluation and management of native VHD. Part II will focus on prosthetic heart valves, infective endocarditis (IE), preoperative assessment of patients with VHD, VHD considerations in children, and future directions.